Serum tri‐ and tetra‐antennary N‐glycan is a potential predictive biomarker for castration‐resistant prostate cancer. Issue 15 (23rd August 2014) - Ishibashi, Yusuke; Tobisawa, Yuki; Hatakeyama, Shingo; Ohashi, Tetsu; Tanaka, Masakazu; Narita, Shintaro; Koie, Takuya; Habuchi, Tomonori; Nishimura, Shin‐Ichiro; Ohyama, Chikara; Yoneyama, Tohru
<x xml:space="preserve">Abstract</x> BACKGROUND The U.S. FDA has approved several novel systemic agents including abiraterone acetate and taxoid cabazitaxel for metastatic castration‐resistant prostate cancer (CRPC) result in a complicated decision‐making while selecting an appropriate treatment. Therefore, a predictive biomarker for CRPC would provide useful information to physicians. The aim of this study is to evaluate the diagnostic potential of serum N‐glycan profiling in CRPC. METHODS Serum N‐glycomics was performed in 80 healthy volunteers and 286 benign prostatic hyperplasia, 258 early‐stage PC, 46 PC with androgen deprivation therapy (ADT), and 68 CRPC patients using the glycoblotting method. A total of 36 types of N‐glycan levels in each patient were analyzed using logistic regression analysis and receiver operating characteristic curves. We also examined the expression of N‐glycan branching enzyme genes in PC cell lines using quantitative RT‐PCR. RESULTS We observed that tri‐ and tetra‐antennary N‐glycans were significantly higher in CRPC patients than in any other groups. The longitudinal follow‐up of tri‐ and tetra‐ antennary N‐glycan levels revealed that one PC with ADT patient showed an increase that was more than the cut‐off level and two consecutive increases in tri‐ and tetra‐antennary N‐glycan levels 3 months apart; resulted in biochemical recurrence despite the castrate level of testosterone, and the patient was defined as CRPC. Expression of N‐glycan branching enzyme genes were significantly upregulated in CRPC cell lines. CONCLUSIONS These results suggest that the overexpression of tri‐ and tetra‐antennary N‐glycan may be associated with the castration‐resistant status in PC and may be a potential predictive biomarker for CRPC. Prostate 74:1521–1529, 2014. © 2014 Wiley Periodicals, Inc.